Penggunaan Smartphone Bermasalah Pada Siswa SMA Serta Implikasinya Bagi Pelayanan Bimbingan dan Konseling di Sekolah - Nira Prihatin Nufus; Susi Fitri; Murti Kusuma Wirasti (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
Excessive use of smartphones can lead to problematic smartphone use. Problematic smartphone use is a person's inability to regulate smartphone use, which results in many negative consequences in everyday life. This study aims to determine the problematic description of smartphone use in high school students in the Bogor area. This research uses a quantitative approach with descriptive methods. The sampling technique was using the purposive sampling technique. The research instrument used was the MPPUSA (Mobile Phone Problem Use Scale for Adolescent) adaptation instrument. Its aspects consist of tolerance, escape from problems, craving, withdrawal, negative consequences, and social motivation. The results of the instrument trial obtained a reliability coefficient of 0.877. The questionnaire was distributed online using the Google Forms application, with 188 respondents (45 male respondents and 143 female respondents). The scale used is the five-point Likert scale. The results showed that the category of problematic use was 8.50%, the users were at risk of 43.62%, habitual use was 40.96%, and occasional users were 6.91%. The highest percentage of problematic smartphone use aspects is the escape from problem aspect of 67.84% and the lowest is the withdrawal aspect of 43.09%. The implication of the results of this study can be used as a needs analysis in making guidance and counseling service programs in schools by guidance and counseling teachers.